Analisis Proses Pembentukan Tujuan Pembelajaran Berdasarkan CP di SD Negeri Empang Bahagia 3 Kota Tangerang - Magdalena, Ina; Salimah, Sumayya Mujahidah; Ezzafira, Rizka (MASALIQ, 2023)
Learning objectives and assessments are core elements of any learning activity. Learning objectives play an important role in providing guidelines for student learning and a basis for evaluation. Before starting certain teaching, the teacher must present or communicate learning objectives to students for various reasons. This study aims to determine the analysis of the process of forming learning objectives based on CP at SD Negeri Empang Bahagia 3 Tangerang City. This study uses a qualitative method. The qualitative method was chosen because the aim is to find out how the learning objectives are formed. The results of the research show that matching and creating coherence between all components of learning objectives helps teachers and students to achieve learning outcomes at SD Negeri Empang Bahagia 3.